Missiological Dialogue in Strategic Decision-Making of the School Principal: A Qualitative Study at UPT SDN 076 Siponjot, Lintongnihuta District, Humbang Hasundutan Regency - Dapot Damanik; Dinar Sianturi; Yohana Nelly Panjaitan; Alex Bob Siringoringo; Kristina Saragih (Jurnal Multidisiplin Sahombu, 2026)
This article explores the integration of "Missiological Dialogue" into the strategic decision-making processes of the School Principal at UPT SDN 076 Siponjot, Lintongnihuta District, Humbang Hasundutan Regency. Strategic decision-making in public primary schools situated within highly religious communities requires an approach that transcends formal managerialism. Using a descriptive qualitative method, this study demonstrates how strategic policies, rooted in the spirit of mission prioritize the holistic development of students and uphold moral integrity to create a transformative educational ecosystem. The findings suggest that Christian Educational Management is not merely a matter of formal identity, but rather a manifestation of the values of love (agape) and justice within every school policy. By aligning governmental mandates with missiological principles, the school functions as a center for social transformation and a witness to ethical leadership in the Humbang Hasundutan region.